CHARACTERIZATION ON OF THE ACCIDENTES OCURRED WITH WORKERS IN A UNIVERSITY HOSPITAL - Emanuelli Mancio Ferreira da Luz; Tânia Solange Bosi de Souza Magnago; Marinez Diniz da Silva Ceron; Fernando Tolfo; Jéssica Baldissera Carollo (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927640 Aim: to characterize work accidents occurred with workers from the University Hospital of Rio Grande do Sul. Methods: cross-sectional study, which data collection occurred in the period July-September 2012, based on Work accidents Notification (2008-2012). For inserting data, we used Epi-info® software and data analysis was developed on PASW Statistics, through descriptive statistics. Results: of the 252 analyzed notifications, there was a prevalence of work accidents among female workers, aged 43 to 66 years old and belonging to the nursing staff. Accidents occurred due to explosion to Koch Bacillus and sharp materials. Conclusions: characterization of accidents allows the elaboration of a diagnosis, which can be used by managers on behalf of the institution as subsidies for permanent education actions on the prevention of accidents at work.